An update of pathogenic variants in ASPM, WDR62, CDK5RAP2, STIL, CENPJ, and CEP135 underlying autosomal recessive primary microcephaly in 32 consanguineous families from Pakistan. Issue 9 (17th July 2020) - Rasool, Sajida; Baig, Jamshaid Mahmood; Moawia, Abubakar; Ahmad, Ilyas; Iqbal, Maria; Waseem, Syeda Seema; Asif, Maria; Abdullah, Uzma; Makhdoom, Ehtisham Ul Haq; Kaygusuz, Emrah; Zakaria, Muhammad; Ramzan, Shafaq; et al.
Abstract: Background: Primary microcephaly (MCPH) is a congenital neurodevelopmental disorder manifesting as small brain and intellectual disability. It underlies isolated reduction of the cerebral cortex that is reminiscent of early hominids which makes it suitable model disease to study the hominin‐specific volumetric expansion of brain. Mutations in 25 genes have been reported to cause this disorder. Although majority of these genes were discovered in the Pakistani population, still a significant proportion of these families remains uninvestigated. Methods: We studied a cohort of 32 MCPH families from different regions of Pakistan. For disease gene identification, genome‐wide linkage analysis, Sanger sequencing, gene panel, and whole‐exome sequencing were performed. Results: By employing these techniques individually or in combination, we were able to discern relevant disease‐causing DNA variants. Collectively, 15 novel mutations were observed in five different MCPH genes; ASPM (10), WDR62 (1), CDK5RAP2 (1), STIL (2), and CEP135 (1). In addition, 16 known mutations were also verified. We reviewed the literature and documented the published mutations in six MCPH genes. Intriguingly, our cohort also revealed a recurrent mutation, c.7782_7783delGA;p.(Lys2595Serfs*6), of ASPM reported worldwide. Drawing from this collective data, we propose two founder mutations, ASPM :c.9557C>G;p.(Ser3186*) and CENPJ :c.18delC;p.(Ser7Profs*2), in the Pakistani population. Conclusions: We discovered novel DNA variants, impairing the function of genes indispensable to build a proper functioning brain. Our study expands the mutational spectra of known MCPH genes and also provides supporting evidence to the pathogenicity of previously reported mutations. These novel DNA variants will be helpful for the clinicians and geneticists for establishing reliable diagnostic strategies for MCPH families. Abstract : Genomic analyses of 32 Pakistani families manifesting primary microcephaly.